Design and Implementation of Decentralized IMC-PI Controllers for Real Time Coupled Tank Process - Datta, S; Nath, U.M; Dey, C (Michael Faraday IET International Summit 2015, 2015)
Decentralized Internal Model Control based Proportional-Integral controllers (IMC-PI) are designed and their performances are evaluated on a real time laboratory scale coupled tank process. It is a well known multi input multi output (MIMO) process with nonlinear behaviour. The experimental quad-coupled tank process is consisting of two upper and two lower tanks. The upper two tanks are connected with two pumps having varying speed drive for supplying water and they have an interacting behaviour with a connection in between them. In this work, our objective is to design and implement two IMC-PI controllers so that the water level can be maintained at the desired positions in the upper two tanks regardless of interaction among them. It is found that merely IMC-PI controllers fail to provide the satisfactory performance due to interaction among the tanks. To reduce interacting behaviour of the coupled tanks, a decoupler is incorporated during closed loop control. Performance of the proposed IMC-PI controllers are tested and compared in presence and absence of the designed decoupler. From the experimental results it is found that in presence of decoupler, IMC-PI controllers are found to provide an overall enhanced performance in maintaining the desired individual tank levels.